Anatomy of a Tuition Freeze: The Case of Ontario - Rexe, Deanna (Canadian Journal of Higher Education, 2015)
Using two conceptual frameworks from political science—Kingdon’s (2003) multiple streams model and the advocacy coalition framework (Sabatier & Jenkins-Smith, 1993)—this case study examines the detailed history of a major tuition policy change in Ontario in 2004: a tuition freeze. The paper explores the social, political, and economic factors that influenced policymakers on this particular change to shed light on the broader questions of the dynamics of postsecondary policymaking. The study found that the Liberal Party’s decision to freeze postsecondary tuition fees was a function of stakeholder relations, public opinion, and brokerage politics, designed for electoral success. The policy implementation strategy was intended to facilitate the cooperation and interests of the major institutions. Within the broader policy community, student-organized interest groups and other policy advocates were aligned in a policy preference, a critical component for successful change.